PENGATURAN PENYELENGGARAAN PEMERINTAHAN DIGITAL DALAM PERSPEKTIF ASAS EFISIENSI DAN EFEKTIVITAS TATA KELOLA PEMERINTAHAN - Bakar, Abu; Syamsir; Arfa'I (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Issues related to the regulation of digital governance from the perspective of the principles of efficiency and effectiveness of governance are very important to discuss because they require appropriate regulations so that the application of digital technology can improve the quality of public services and accelerate bureaucratic processes optimally. The research method used in this study is the normative juridical method, namely by combining the legislative approach and the conceptual approach. In the data collection stage, researchers collected primary legal materials such as laws, secondary legal materials in the form of journals or legal books, and tertiary legal materials such as legal encyclopedias and dictionaries. All collected legal data and information were then analyzed using qualitative analysis methods to gain a deep understanding of the issues studied. The results obtained are that the regulation of digital governance from the perspective of the principles of efficiency of governance is an effort to ensure faster, more transparent and effective administrative processes and public services by utilizing information technology. This also aims to reduce complicated bureaucracy and improve the quality of services to the public and the regulation of digital government administration from the perspective of the principle of effective governance is an effort to ensure that the implementation of information technology in public administration is able to increase transparency, efficiency, and accountability, while providing faster, easier and more targeted public services.